Analysis of The Effect of Service Quality, Trust and Price Perception Through ssCustomer Satisfaction on Customer (Study on Ende Services Client Surabaya) - Kiik, Nita Griselda; Susanti, Nanis; Cempena, I.B. (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
One of the things that drives service is quality which makes one of the very important factors, from this quality brings out a sense of satisfaction for customers. The purpose in this is to find out the influence in the quality of i service with the loyalty ifelt by the customers. The research was conducted using data in the form of primers with sources in the form of direct observations and with questionnaires produced to the respondents. The results in this study are the influence of quality, trust, price perception, customer satisfaction on customer loyalty.